High-temperature-resistant silicon oxide aerogel thermal insulation felt and preparation method thereof

CN118125795BActive Publication Date: 2026-10-20CHANGSHA RONGLAN MACHINERY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410493626.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-23
Publication Date
2026-10-20
Estimated Expiration
2044-04-23

AI Technical Summary

Technical Problem

但是,现有方法制备的氧化硅气凝胶在高温下易发生烧结、致密化和孔结构坍塌,导致尺寸收缩和隔热性能下降,因而氧化硅气凝胶隔热毡长期使用温度局限在700℃以下,无法满足更高温度下的隔热需求

Benefits of technology

[0045]a)可得到高纯度、水含量极少的醇性氧化硅溶胶。采用高温高压方式促使水解液中的原料完全反应形成纳米氧化硅粒子和乙醇(副产物),从而得到高纯度的醇性氧化硅溶胶,加少量酸或碱后即可得到氧化硅凝胶,从源头上保证了杂质含量很少。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118125795B_ABST
    Figure CN118125795B_ABST
Patent Text Reader

Abstract

The application discloses a high-temperature-resistant silicon oxide aerogel heat-insulating felt and a preparation method thereof. The method comprises the following steps: S1, a catalyst solution is added into a prepared monodisperse silica sol of an alcohol solvent system, and stirring is uniformly performed to obtain a silica sol; the solvent of the catalyst solution is an alcohol solvent; S2, a surfactant is added into the silica sol and stirring is uniformly performed, then light shielding agent particles are added into the silica sol, and stirring is uniformly performed to form a silica sol containing the light shielding agent; S3, a ceramic fiber felt is immersed in the silica sol containing the light shielding agent to perform gel aging, and a fiber felt / gel composite is obtained; and S4, the fiber felt / gel composite is dried to obtain the high-temperature-resistant silicon oxide aerogel heat-insulating felt. The heat-insulating felt prepared by the method has the characteristics of high-temperature resistance (1100 DEG C), excellent heat-insulating performance, good flexibility, simple installation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of high-temperature thermal insulation technology, and in particular to a high-temperature resistant silica aerogel thermal insulation felt and its preparation method. Background Technology

[0002] Aerogels possess a unique nanoporous structure and are currently the solid materials with the lowest thermal conductivity at room temperature (as low as 0.013 W / (m·K)). Since the early 20th century, silica aerogel insulation felts with fibers as the reinforcing phase have been industrialized, exhibiting thermal insulation performance 2 to 4 times that of traditional materials (rock wool, glass wool, perlite, etc.), and have been widely used in the field of thermal insulation for petrochemical pipelines. However, silica aerogels prepared by existing methods are prone to sintering, densification, and pore structure collapse at high temperatures, leading to dimensional shrinkage and a decrease in thermal insulation performance. Consequently, the long-term operating temperature of silica aerogel insulation felts is limited to below 700℃, failing to meet the thermal insulation requirements at higher temperatures. Furthermore, existing silica aerogel insulation felts exhibit a shrinkage rate exceeding 5% after heat treatment at 900℃ for 2 hours, and their thermal conductivity increases significantly at high temperatures, reaching over 0.085 and 0.136 W / (m·K) at 800℃ and 1000℃, respectively, indicating that their high-temperature thermal insulation performance still needs further improvement. Summary of the Invention

[0003] This invention provides a high-temperature resistant silica aerogel insulation felt and its preparation method. The silica aerogel insulation felt prepared by this invention has the characteristics of high temperature resistance up to 1100℃, excellent thermal insulation performance, good flexibility, and easy installation. It has broad application prospects in aerospace high-temperature insulation, civil kiln insulation and other fields.

[0004] To achieve the above objectives, this invention proposes a method for preparing a high-temperature resistant silica aerogel insulation felt, comprising the following steps:

[0005] S1. A monodisperse silica sol in an alcohol solvent system is prepared by an alcohol thermal method, and then an alkaline catalyst solution is added to it and stirred evenly to obtain silica sol; the solvent of the catalyst solution is an alcohol solvent; the average particle size of the monodisperse silica sol is 10-120 nm; the deviation between the minimum and maximum particle size and the average particle size is less than 20%.

[0006] S2. Add the surfactant to the silica sol and stir until homogeneous. Then add the opaque particles to the silica sol and stir until homogeneous to form a silica sol containing opaque agent.

[0007] S3. The ceramic fiber felt is immersed in silica sol containing a light-blocking agent for gel aging to obtain a fiber felt / gel composite.

[0008] S4. The fiber felt / gel composite is dried to obtain high-temperature resistant silica aerogel insulation felt.

[0009] The present invention also proposes a high-temperature resistant silica aerogel insulation felt, which is prepared by the above-described method.

[0010] In summary, this invention uses monodisperse silica sol (silica sol with narrow particle size distribution) in an alcohol solvent system as the main raw material and high-temperature resistant ceramic fiber felt as the reinforcing phase to prepare silica aerogel insulation felt through a simple and rapid process of sol-fiber impregnation, rapid aging, and supercritical carbon dioxide drying. The beneficial effects of this invention are as follows:

[0011] 1. Using monodisperse silica sol in an alcohol solvent system as the main raw material, and adding an alkali as a catalyst, gels the silica aerogel to form a well-developed nanoporous network structure. Compared with silica sol prepared by conventional methods, the silica sol using an alcohol solvent system has a very low water content, resulting in minimal capillary force generated by the drying medium during supercritical drying, leading to silica aerogels with better bulkness and porous network structure. The silica particles in the monodisperse silica sol have better uniformity in size, resulting in a more uniform pore size distribution and network structure in the aerogel. When using silica sol with a larger average particle size (above 10 nm), the resulting silica aerogel nanoparticles have relatively lower activity. Furthermore, due to the highly uniform particle size and pore size, the sintering stress difference is significantly reduced, thus significantly enhancing the aerogel's resistance to sintering at high temperatures, resulting in a significantly higher operating temperature compared to conventional silica aerogels. The entire sol preparation process involves only one step, requiring only the addition of a catalyst to the silica sol, making the process simple and short-cycle.

[0012] 2. Using highly flexible ceramic fiber felt as the reinforcing phase and as a high-temperature resistant fiber skeleton, the ability of silica aerogel to resist sintering at high temperatures is further improved, the dimensional shrinkage of aerogel insulation felt at high temperatures is reduced, and aerogel insulation felt is endowed with good formability and flexibility.

[0013] 3. Introducing a high-temperature resistant light-blocking agent into silica aerogel insulation felt significantly improves the insulation felt's ability to block infrared radiation and reduces its high-temperature thermal conductivity. The light-blocking agent is dispersed in silica sol through a simple sol-gel mixing and stirring process, and then impregnated into the pores of the fiber felt under normal pressure, thus ensuring the light-blocking agent is evenly distributed throughout the insulation felt. This method effectively achieves uniform introduction of the light-blocking agent into the fiber felt.

[0014] After adding an appropriate amount of surfactant to the silica sol, the opacifier particles are added to the sol and stirred until homogeneous. The fiber mat is then immersed in the sol, and after the sol has fully penetrated, it is rapidly aged to form a gel / fiber mat composite doped with opacifier.

[0015] Surfactant molecules, composed of hydrophilic and lipophilic ends, can significantly improve the compatibility and uniformity of mixtures of polar and nonpolar substances, allowing opacifier particles to be stably and uniformly suspended in silica sol. Surfactants can also reduce the surface energy of the sol, increasing its wettability with the fiber mat and enabling rapid penetration.

[0016] 4. This solution utilizes readily available raw materials, employs a simple process, has a short preparation cycle, and is easily mass-produced. The prepared silica aerogel insulation felt can withstand temperatures up to 1100℃ while exhibiting very low high-temperature thermal conductivity and good flexibility. The thickness shrinkage after treatment at 1100℃ for 2 hours is less than 3%; typical thermal conductivity values ​​at 800℃, 1000℃, and 1100℃ are 0.05 W / (m·K), 0.074 W / (m·K), and 0.080 W / (m·K), respectively, representing a reduction of over 30% compared to existing silica aerogel insulation felts; tensile strength reaches over 0.2 MPa, and compression resilience exceeds 90%; the molding size can reach 40m in length, 1500mm in width, and 30mm in thickness, allowing for rapid cutting and installation; a 20mm thick silica aerogel insulation felt, after being heated to 1100℃ on one side for 1800s, can achieve a cold surface temperature below 320℃. Attached Figure Description

[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0018] Figure 1 Photograph of the silica aerogel insulation felt of Example 1;

[0019] Figure 2 This is a photograph of the silica aerogel insulation felt in Example 2 before heat treatment at 1100℃;

[0020] Figure 3 This is a photograph of the silica aerogel insulation felt of Example 2 after heat treatment at 1100°C;

[0021] Figure 4 This is a scanning electron microscope image of the silica aerogel in Example 3.

[0022] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0023] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0024] Furthermore, the technical solutions of the various embodiments of the present invention can be combined with each other, but only if they are feasible for those skilled in the art. If the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention.

[0025] Unless otherwise specified, all raw materials used in this invention are commercially available.

[0026] This invention proposes a method for preparing a high-temperature resistant silica aerogel insulation felt, comprising the following steps:

[0027] S1. Monodisperse silica sol in an alcohol solvent system is prepared by the alcohol thermal method, and then an alkaline catalyst solution is added to it and stirred evenly to obtain silica sol.

[0028] The solvent for the catalyst solution is an alcohol solvent.

[0029] The average particle size of monodisperse silica sol is 10–120 nm. When the particle size of monodisperse silica sol is less than 10 nm, the temperature resistance of the prepared silica aerogel is not significantly improved compared with conventional silica aerogel; when the particle size is greater than 120 nm, silica sol is difficult to gel, and the prepared silica aerogel has poor bulking and strength.

[0030] The deviation between the minimum and maximum particle size and the average particle size should be less than 20%. The particle size distribution should be concentrated, and the deviation between the minimum and maximum particle size and the average particle size should be less than 20%. If the deviation is too large, the sintering stress of the nanoparticle units of the prepared silica aerogel will increase at high temperature, and the temperature resistance of the aerogel will be adversely affected.

[0031] S2. Add the surfactant to the silica sol and stir until homogeneous. Then add the opaque particles to the silica sol and stir until homogeneous to form a silica sol containing opaque agent.

[0032] S3. The ceramic fiber felt is immersed in silica sol containing a light-blocking agent for gel aging to obtain a fiber felt / gel composite.

[0033] S4. The fiber felt / gel composite is dried to obtain high-temperature resistant silica aerogel insulation felt.

[0034] Preferably, in step S1, the preparation of the monodisperse silica sol in the alcohol solvent system using the alcohol thermal method specifically includes the following steps:

[0035] 1) Add the silicon source precursor to the alcohol solvent and stir to mix evenly to obtain a silicon source precursor solution;

[0036] 2) Add the aqueous acid solution dropwise to the silicon source precursor solution and react at room temperature for 1–24 h to obtain the hydrolysate;

[0037] 3) Pour the hydrolysate into a high-pressure reactor, seal it, heat it to 80-275℃ and maintain it for 0.5-24 hours, then let it cool naturally to obtain monodisperse silica sol.

[0038] When the alcoholic temperature is below 80℃, the average particle size of the obtained silica sol particles is relatively small; when the alcoholic temperature is above 275℃, the average particle size of the obtained silica sol particles is relatively large and they are prone to precipitation, resulting in poor sol stability.

[0039] The alcohol heating time is greater than 24 hours, resulting in an excessively long preparation cycle.

[0040] During the alcohol heating process, the atmosphere is air, and the pressure inside the vessel naturally increases as the temperature rises, ranging from 0.1 to 10 MPa.

[0041] 4) Add a desiccant to the monodisperse silica sol and keep stirring for 1 to 24 hours.

[0042] If the stirring time is less than 1 hour, insufficient water absorption will result in a high residual moisture content in the sol; if the stirring time is greater than 24 hours, the excessive water removal time will affect the preparation efficiency.

[0043] 5) Filter the desiccant containing water of crystallization to obtain a high-purity monodisperse silica sol with alcohol as the dispersion medium.

[0044] The preparation of monodisperse silica sol in an alcohol solvent system using the above process has the following beneficial effects:

[0045] a) High-purity alcoholic silica sol with extremely low water content can be obtained. A high-temperature, high-pressure process is used to ensure the complete reaction of the raw materials in the hydrolysate, forming nano-silica particles and ethanol (a byproduct), thus obtaining a high-purity alcoholic silica sol. Adding a small amount of acid or alkali yields silica gel, ensuring a very low impurity content from the outset.

[0046] b) The process is simple and inexpensive. Using alcohol-based silica sol to prepare silica aerogel avoids complex displacement processes, allowing for direct supercritical drying after aging.

[0047] c) By simply heating and pressurizing, the silica particles in the hydrolysate can be grown and homogenized, thereby obtaining a monodisperse silica sol with a narrow particle size distribution.

[0048] Preferably, in steps 1) to 4), the molar ratio of silicon source precursor: alcohol solvent: acid: water is 1:(3-30):(0.0005-0.01):(3-15).

[0049] When the molar ratio of silicon source precursor to alcohol solvent is less than 1:30, the resulting monodisperse silica sol has a low solid content and is difficult to form a gel; when the molar ratio is greater than 1:3, the concentration of reactants is high, and they are prone to aggregation and precipitation, making it difficult to form a stable sol.

[0050] When the molar ratio of silicon source precursor to acid is less than 1:0.0005, the catalytic effect is weak, and the hydrolysis reaction of silicon source precursor is slow or cannot be hydrolyzed; when the molar ratio is greater than 1:0.01, the hydrolysis reaction of silicon source precursor is too fast and difficult to control, and large particles are easily generated, making it difficult to form a stable sol.

[0051] When the molar ratio of silicon precursor to water is less than 1:15, the hydrolysis reaction of the silicon precursor is too fast and difficult to control, easily producing large particles and making it difficult to form a stable sol; when the molar ratio is greater than 1:3, the hydrolysis reaction of the silicon precursor is insufficient and it is difficult to obtain a high-purity silica sol.

[0052] The molar ratio of water to absorbent is 1:(1-6). When the molar ratio is greater than 1:1, the water absorption effect is insufficient; when it is less than 1:6, the consumption of absorbent is too high.

[0053] Preferably, the silicon source precursor is any one of tetraethyl orthosilicate, methyl orthosilicate, butyl orthosilicate, and polyethyl orthosilicate;

[0054] The alcohol solvent is any one of ethanol, isopropanol, n-propanol, n-butanol, sec-butanol, and tert-butanol;

[0055] The acid is any one of nitric acid, hydrochloric acid, acetic acid, sulfuric acid, and hydrofluoric acid;

[0056] The absorbent can be any one of sodium sulfate, calcium sulfate, calcium chloride, magnesium sulfate, copper sulfate, and potassium carbonate.

[0057] Preferably, in step S1, the solid content of the monodisperse silica sol is 5-30%. When it is below 5%, gelation is not easy to occur, and the density and structural strength of the prepared aerogel are low, resulting in insufficient strength of the thermal insulation felt; when it is above 30%, the density and thermal conductivity of the prepared aerogel are high, resulting in high thermal conductivity of the thermal insulation felt.

[0058] Preferably, in step S1, the concentration of the catalyst solution is 0.005 to 1 mol / L. When the concentration is below 0.005 mol / L, the amount of catalyst solution added will be very high, which will significantly dilute the monodisperse silica sol and reduce the density and strength of the resulting silica aerogel. When the concentration is above 1 mol / L, the catalyst concentration in the monodisperse silica sol is easily too high in some areas during the addition process, resulting in large particles.

[0059] Preferably, in step S1, the molar ratio of the catalyst to the silica particles in the monodisperse silica sol is 0.001 to 0.1:1. Below 0.001:1, the sol is difficult to gel or does not gel, while above 0.1:1, the viscosity of the sol rises rapidly and gels, making it impossible to impregnate the ceramic fiber felt.

[0060] Preferably, in step S1, the alcohol solvent is any one of ethanol, isopropanol, n-propanol, n-butanol, sec-butanol, and tert-butanol;

[0061] The alkaline catalyst is ammonia.

[0062] Preferably, in step S2, the mass ratio of surfactant to silica sol is 0.2 to 3:100, which ensures that the opacifier has a good dispersion effect in the sol, while the cost of surfactant raw materials is low.

[0063] The mass ratio of light-blocking agent particles to silica sol is 0.5 to 6:100, which can ensure the best infrared radiation blocking effect without significantly increasing solid heat conduction. Aerogel insulation felt has the lowest overall thermal conductivity.

[0064] The average diameter of the opaque agent particles ranges from 0.4 to 6 μm. Within this range, the opaque agent has the best blocking effect on infrared radiation waves corresponding to the temperature range of 300 to 1100°C. Moreover, the opaque agent itself does not significantly increase the solid-state thermal conductivity of the insulation felt, and can significantly reduce the overall thermal conductivity of the insulation felt within this temperature range.

[0065] Preferably, in step S2, the surfactant is any one of sodium oleate, sodium alkyl succinic anhydride, sodium cocoate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium secondary alkyl sulfonate, dodecyl trimethyl ammonium chloride, dodecyl dimethyl benzyl ammonium chloride, didodecyl dimethyl ammonium chloride, dodecyl glucoside, fatty alcohol polyoxyethylene ether glucoside, dodecyl betaine, dodecyl dimethyl ammonium chloride, dodecyl dimethyl ammonium oxide, fatty alcohol polyoxyethylene ether, and dodecylphenol polyoxyethylene ether.

[0066] Preferably, in step S2, the light-blocking agent particles are any one of silicon carbide, zirconium oxide, titanium oxide, boron carbide, and boron nitride.

[0067] Preferably, step S3 specifically includes:

[0068] Under normal pressure, ceramic fiber felt is immersed in silica sol containing a light-blocking agent for 0.5–30 min to gel, and then kept at room temperature to 75°C for 0.5–2 h to obtain a fiber felt / gel composite. The immersion state for 0.5–30 min can achieve sufficient impregnation effect and the impregnation cycle is short. After gelation, keeping it at room temperature to 75°C for 0.5–2 h can achieve complete gelation and a short aging cycle.

[0069] Among them, ceramic fiber felt is any one of alumina fiber felt, mullite fiber felt, high silica fiber felt, aluminum silicate fiber felt, and quartz fiber felt.

[0070] Preferably, in step S3, the drying process specifically involves placing the fiber felt / gel composite in a supercritical drying vessel and sealing it, using carbon dioxide fluid as the drying medium.

[0071] The temperature inside the vessel is 40–80℃, the pressure is 10–25MPa, and the holding time is 6–24h.

[0072] Setting the above temperature, pressure, and holding time ensures that the carbon dioxide fluid can fully replace the liquid in the gel pores and achieves high drying efficiency.

[0073] Silica aerogel is obtained by supercritical carbon dioxide drying. During this process, the continuously circulating carbon dioxide fluid exchanges with the liquid in the pores of the silica aerogel, while carrying away organic impurities, so that the pores are completely filled with carbon dioxide fluid. Then, the carbon dioxide fluid is discharged by depressurization. Therefore, silica aerogel with almost no impurities can be obtained, and no further heat treatment is required.

[0074] The present invention also proposes a high-temperature resistant silica aerogel insulation felt, which is prepared by the above-described method.

[0075] Example 1

[0076] The first step is the preparation of monodisperse silica sol.

[0077] 1) Add tetraethyl orthosilicate to isopropanol and stir to mix evenly to obtain a tetraethyl orthosilicate solution;

[0078] 2) Add an aqueous solution of nitric acid dropwise to a tetraethyl orthosilicate solution and react at room temperature for 2 hours to obtain a hydrolysate. The molar ratio of tetraethyl orthosilicate:isopropanol:nitric acid:water is 1:4:0.005:10.

[0079] 3) Pour the hydrolysate into a high-pressure reactor, seal it, heat it to 195℃ and maintain it for 4 hours, then let it cool naturally to obtain monodisperse silica sol.

[0080] 4) Add sodium sulfate to the monodisperse silica sol and stir for 6 hours. The molar ratio of water to sodium sulfate is 1:2.

[0081] 5) The sodium sulfate containing water of crystallization was filtered to obtain a high-purity monodisperse silica sol with isopropanol as the dispersion medium. The sol had a particle size (average particle size) of 75 nm, a solid content of 14%, and the deviation between the minimum and maximum particle sizes and the average particle size was 12%.

[0082] The second step is the preparation of silica sol.

[0083] Ammonia water was added to the monodisperse silica sol and stirred until homogeneous to obtain silica sol.

[0084] The solvent for the ammonia solution is isopropanol, with a concentration of 0.02 mol / L. The molar ratio of ammonia solution to silicon dioxide is 0.05:1.

[0085] The third step is to add a sunscreen.

[0086] Fatty alcohol polyoxyethylene ether glucoside was added to the silica sol obtained in the first step and stirred until homogeneous. Zirconia particles were then added to the sol and stirred until homogeneous to form a sol containing zirconia particles. The mass ratio of fatty alcohol polyoxyethylene ether glucoside to silica sol was 1:100. The diameter of the zirconia particles was 1.4 μm, and the mass ratio of the zirconia particles to the silica sol was 1.5:100.

[0087] The fourth step is sol impregnation and gel aging.

[0088] Under normal pressure, quartz fiber felt was immersed in silica sol with added zirconium oxide particles for 8 minutes and gelled. Then, it was kept at room temperature for 1.5 hours to obtain fiber felt / gel composite.

[0089] Step 5: Supercritical drying.

[0090] The fiber felt / gel composite was placed in a supercritical drying autoclave and sealed, using carbon dioxide fluid as the drying medium. The temperature inside the autoclave was 60℃, the pressure was 15MPa, and the holding time was 10h. After drying, silica aerogel insulation felt was obtained.

[0091] The silica aerogel insulation felt prepared in Example 1 has a density of 0.26 g / cm³. 3It can withstand temperatures up to 1100℃ while exhibiting very low high-temperature thermal conductivity and good flexibility. The thickness shrinkage rate after treatment at 1100℃ for 2 hours is 2.4%; the thermal conductivity at 800, 1000, and 1100℃ is 0.05, 0.074, and 0.080 W / (m·K), respectively; the tensile strength is 0.28 MPa, and the compression resilience reaches 94%, allowing for rapid cutting and quick wrapping installation. A 20mm thick silica aerogel insulation felt, after being heated to 1100℃ on one side for 1800 seconds, has a cold surface temperature of 316℃.

[0092] Figure 1 The image shows the silica aerogel insulation felt prepared in Example 1. It has a smooth and uniform surface, dimensions of 600×400×3mm, and uniform thickness.

[0093] Example 2

[0094] The first step is the preparation of monodisperse silica sol.

[0095] 1) Add tetraethyl orthosilicate to isopropanol and stir to mix evenly to obtain a tetraethyl orthosilicate solution;

[0096] 2) Add an aqueous solution of nitric acid dropwise to a tetraethyl orthosilicate solution and react at room temperature for 2 hours to obtain a hydrolysate. The molar ratio of tetraethyl orthosilicate:isopropanol:nitric acid:water is 1:5:0.003:12.

[0097] 3) Pour the hydrolysate into a high-pressure reactor, seal it, heat it to 250℃ and maintain it for 6 hours, then let it cool naturally to obtain monodisperse silica sol.

[0098] 4) Add calcium chloride to the monodisperse silica sol and stir for 10 hours. The molar ratio of water to calcium chloride is 1:2.

[0099] 5) Filter the calcium chloride containing water of crystallization to obtain a high-purity monodisperse silica sol with isopropanol as the dispersion medium. The sol has a particle size (average particle size) of 105 nm, a solid content of 14%, and the deviation between the minimum and maximum particle sizes and the average particle size is 12%.

[0100] The second step is the preparation of silica sol.

[0101] Ammonia water was added to the monodisperse silica sol and stirred until homogeneous to obtain silica sol.

[0102] The solvent for the ammonia solution is isopropanol, with a concentration of 0.02 mol / L. The molar ratio of ammonia solution to silicon dioxide is 0.05:1.

[0103] The third step is to add a sunscreen.

[0104] Fatty alcohol polyoxyethylene ether glucoside was added to the silica sol obtained in the first step and stirred until homogeneous. Zirconia particles were then added to the sol and stirred until homogeneous to form a sol containing zirconia particles. The mass ratio of fatty alcohol polyoxyethylene ether glucoside to silica sol was 1:100. The diameter of the zirconia particles was 1.4 μm, and the mass ratio of the zirconia particles to the silica sol was 1.5:100.

[0105] The fourth step is sol impregnation and gel aging. Under normal pressure, the quartz fiber felt is immersed in silica sol containing zirconium oxide particles for 8 minutes to induce gelation, and then kept at room temperature for 1.5 hours to obtain the fiber felt / gel composite.

[0106] Step 5: Supercritical drying.

[0107] The fiber felt / gel composite was placed in a supercritical drying autoclave and sealed, using carbon dioxide fluid as the drying medium. The temperature inside the autoclave was 60℃, the pressure was 15MPa, and the holding time was 10h. After drying, silica aerogel insulation felt was obtained.

[0108] The silica aerogel insulation felt prepared in Example 2 has a density of 0.27 g / cm³. 3 The thickness shrinkage rate after treatment at 1100℃ for 2 hours is 0.1%; the thermal conductivity at 800, 1000, and 1100℃ is 0.054, 0.079, and 0.089 W / (m·K), respectively; and the tensile strength is 0.20 MPa. A 20 mm thick silica aerogel insulation felt, after being heated on one side at 1100℃ for 1800 seconds, has a cold surface temperature of 354℃.

[0109] Figure 2 , Figure 3 The images show photos of the silica aerogel insulation felt from Example 2 before and after treatment at 1100℃. After heat treatment at 1100℃ for 2 hours, the aerogel insulation felt showed no significant changes in appearance, with no deformation, cracking, or delamination. The dimensional shrinkage in the length, width, and thickness directions was only 0.1%, 0.0%, and 0.1%, respectively, indicating that it has excellent temperature resistance.

[0110] Example 3

[0111] The first step is the preparation of monodisperse silica sol.

[0112] 1) Add tetraethyl orthosilicate to isobutanol and stir to mix evenly to obtain a tetraethyl orthosilicate solution;

[0113] 2) Add an aqueous solution of nitric acid dropwise to a tetraethyl orthosilicate solution and react at room temperature for 2 hours to obtain a hydrolysate. The molar ratio of tetraethyl orthosilicate:isopropanol:nitric acid:water is 1:4:0.002:6.

[0114] 3) Pour the hydrolysate into a high-pressure reactor, seal it, heat it to 105℃ and maintain it for 4 hours, then let it cool naturally to obtain monodisperse silica sol.

[0115] 4) Add sodium sulfate to the monodisperse silica sol and stir for 6 hours. The molar ratio of water to sodium sulfate is 1:2.

[0116] 5) The sodium sulfate containing water of crystallization was filtered to obtain a high-purity monodisperse silica sol with isobutanol as the dispersion medium. The sol had a particle size (average particle size) of 35 nm, a solid content of 12%, and the deviation between the minimum and maximum particle sizes and the average particle size was 10%.

[0117] The second step is the preparation of silica sol.

[0118] Ammonia water was added to the monodisperse silica sol and stirred until homogeneous to obtain silica sol.

[0119] The solvent for ammonia is isopropanol with a concentration of 0.02 mol / L, and the molar ratio of nitric acid to silicon dioxide is 0.05:1.

[0120] The third step is to add a sunscreen.

[0121] Fatty alcohol polyoxyethylene ether glucoside was added to the silica sol obtained in the first step and stirred until homogeneous. Zirconia particles were then added to the sol and stirred until homogeneous to form a sol containing zirconia particles. The mass ratio of fatty alcohol polyoxyethylene ether glucoside to silica sol was 1:100. The diameter of the zirconia particles was 1.4 μm, and the mass ratio of the zirconia particles to the silica sol was 1.5:100.

[0122] The fourth step is sol impregnation and gel aging. Under normal pressure, alumina fiber felt is immersed in silica sol containing zirconium oxide particles for 8 minutes to induce gelation, and then kept at room temperature for 1.5 hours to obtain the fiber felt / gel composite.

[0123] Step 5: Supercritical drying.

[0124] The fiber felt / gel composite was placed in a supercritical drying autoclave and sealed, using carbon dioxide fluid as the drying medium. The temperature inside the autoclave was 60℃, the pressure was 15MPa, and the holding time was 10h. After drying, silica aerogel insulation felt was obtained.

[0125] Figure 4 The image shown is a scanning electron microscope image of the silica aerogel in Example 3. It shows that the particle size and pore size of the aerogel are very uniform, which is beneficial for the aerogel to maintain a very low thermal conductivity and reduce its sintering stress in high-temperature environments, thereby improving its temperature resistance.

[0126] The silica aerogel insulation felt prepared in Example 3 has a density of 0.24 g / cm³.3 It can withstand temperatures up to 1100℃ while exhibiting very low high-temperature thermal conductivity and good flexibility. The thickness shrinkage rate after treatment at 1100℃ for 2 hours is 0.3%; the thermal conductivity at 800, 1000, and 1100℃ is 0.057, 0.082, and 0.094 W / (m·K), respectively; the tensile strength is 0.23 MPa, and the compression resilience is 91%. A 20mm thick silica aerogel insulation felt, after being heated to 1100℃ on one side for 1800 seconds, has a cold surface temperature of 368℃.

[0127] Example 4

[0128] The first step is the preparation of monodisperse silica sol.

[0129] 1) Add tetraethyl orthosilicate to isopropanol and stir to mix evenly to obtain a tetraethyl orthosilicate solution;

[0130] 2) Add an aqueous solution of nitric acid dropwise to a tetraethyl orthosilicate solution and react at room temperature for 2 hours to obtain a hydrolysate. The molar ratio of tetraethyl orthosilicate:isopropanol:nitric acid:water is 1:4:0.005:10.

[0131] 3) Pour the hydrolysate into a high-pressure reactor, seal it, heat it to 195℃ and maintain it for 4 hours, then let it cool naturally to obtain monodisperse silica sol.

[0132] 4) Add sodium sulfate to the monodisperse silica sol and stir for 6 hours. The molar ratio of water to sodium sulfate is 1:2.

[0133] 5) The sodium sulfate containing water of crystallization was filtered to obtain a high-purity monodisperse silica sol with isopropanol as the dispersion medium. The sol had a particle size (average particle size) of 75 nm, a solid content of 14%, and the deviation between the minimum and maximum particle sizes and the average particle size was 12%.

[0134] The first step is to prepare the silica sol.

[0135] Hydrochloric acid solution was added to monodisperse silica sol and stirred until homogeneous to obtain silica sol.

[0136] The solvent for the hydrochloric acid solution is isopropanol, with a concentration of 0.02 mol / L, and the molar ratio of hydrochloric acid to silicon dioxide is 0.05:1.

[0137] The second step is to add a light-blocking agent.

[0138] Sodium dodecylbenzenesulfonate was added to the silica sol obtained in the first step and stirred until homogeneous. Then, silicon carbide particles were added to the sol and stirred until homogeneous to form a sol containing silicon carbide particles. The mass ratio of fatty alcohol polyoxyethylene ether glucoside to silica sol was 1:100. The diameter of the silicon carbide particles was 1.4 μm, and the mass ratio of the silicon carbide particles to the silica sol was 1.5:100.

[0139] The third step is sol impregnation and gel aging.

[0140] Under normal pressure, quartz fiber felt was immersed in silica sol with added silicon carbide particles for 25 minutes and gelled. Then, it was kept at room temperature for 1 hour to obtain a fiber felt / gel composite.

[0141] The fourth step is supercritical drying.

[0142] The fiber felt / gel composite was placed in a supercritical drying autoclave and sealed, using carbon dioxide fluid as the drying medium. The temperature inside the autoclave was 65℃, the pressure was 18MPa, and the holding time was 8h. After drying, silica aerogel insulation felt was obtained.

[0143] The silica aerogel insulation felt prepared in Example 4 has a density of 0.27 g / cm³. 3 The thickness shrinkage rate after treatment at 1100℃ for 2 hours is 2.7%; the thermal conductivity at 800, 1000, and 1100℃ is 0.048, 0.071, and 0.076 W / (m·K), respectively, and the tensile strength is 0.34 MPa. A 20 mm thick silica aerogel insulation felt, after being heated to 1100℃ on one side for 1800 seconds, has a cold surface temperature of 302℃.

[0144] Comparative Example 1

[0145] The difference between Comparative Example 1 and Example 1 is that the solvent for the monodisperse silica sol is water. The silica aerogel insulation felt prepared in Comparative Example 1 has thermal conductivity of 0.062 and 0.105 W / (m·K) at 800 and 1100 °C, respectively.

[0146] Comparative Example 2

[0147] Compared to Example 1, Comparative Example 2 differs in that the alcohol heating temperature is 60°C, resulting in a monodisperse silica sol particle size of 7 nm. The silica aerogel insulation felt prepared in Comparative Example 1 exhibited a thickness shrinkage rate of 6.1% after treatment at 1100°C for 2 hours.

[0148] Comparative Example 3

[0149] Compared with Example 1, Comparative Example 3 differs in that the deviation between the maximum, minimum, and average particle sizes of the monodisperse silica sol is greater than 20%. The silica aerogel insulation felt prepared in Comparative Example 3, after being treated at 1100℃ for 2 hours, exhibits a thickness shrinkage rate higher than 3.5%.

[0150] Table 1 provides a comparison of the product performance of Examples 1-4 and Comparative Examples 1-3.

[0151] Table 1 Comparison of product performance in Examples 1-4 and Comparative Examples 1-3

[0152]

[0153]

[0154] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for preparing a high-temperature resistant silica aerogel insulation felt, characterized in that, Includes the following steps: S1. A monodisperse silica sol in an alcohol solvent system is prepared by an alcohol thermal method, and then an alkaline catalyst solution is added to it and stirred until homogeneous to obtain silica sol; the solvent of the catalyst solution is an alcohol solvent; the average particle size of the monodisperse silica sol is 10~120nm; the deviation between the minimum and maximum particle size and the average particle size is less than 20%; S2. Add the surfactant to the silica sol and stir until homogeneous. Then add the opaque particles to the silica sol and stir until homogeneous to form a silica sol containing opaque agent. S3. The ceramic fiber felt is immersed in silica sol containing a light-blocking agent for gel aging to obtain a fiber felt / gel composite. S4. Dry the fiber felt / gel composite to obtain high-temperature resistant silica aerogel insulation felt. In step S1, a monodisperse silica sol in an alcohol solvent system is prepared using an alcohol thermal method, specifically including the following steps: 1) Add the silicon source precursor to the alcohol solvent and stir to mix evenly to obtain a silicon source precursor solution; 2) Add the aqueous acid solution dropwise to the silicon source precursor solution and react at room temperature for 1-24 hours to obtain the hydrolysate; 3) Pour the hydrolysate into a high-pressure reactor, seal it, heat it to 80-275℃ and maintain it for 0.5-24 hours, then let it cool naturally to obtain monodisperse silica sol; 4) Add a desiccant to the monodisperse silica sol and keep stirring for 1~24 hours; 5) Filter the desiccant containing water of crystallization to obtain a high-purity monodisperse silica sol with alcohol as the dispersion medium; The molar ratio of silicon source precursor: alcohol solvent: acid: water is 1: (3~30): (0.0005~0.01): (3~15). The molar ratio of water to absorbent is 1:(1~6).

2. The preparation method according to claim 1, characterized in that, The silicon source precursor is any one of tetraethyl orthosilicate, methyl orthosilicate, butyl orthosilicate, and polyethyl orthosilicate; The alcohol solvent is any one of ethanol, isopropanol, n-propanol, n-butanol, sec-butanol, and tert-butanol; The acid is any one of nitric acid, hydrochloric acid, acetic acid, sulfuric acid, and hydrofluoric acid; The absorbent is any one of sodium sulfate, calcium sulfate, calcium chloride, magnesium sulfate, copper sulfate, and potassium carbonate.

3. The preparation method according to claim 1, characterized in that, In step S1, the solid content of the monodisperse silica sol is 5-30%; The concentration of the catalyst solution is 0.005~1 mol / L; The molar ratio of the catalyst to the silica particles in the monodisperse silica sol is 0.001~0.1:1; The alcohol solvent is any one of ethanol, isopropanol, n-propanol, n-butanol, sec-butanol, and tert-butanol.

4. The preparation method according to claim 1, characterized in that, In step S2, the mass ratio of surfactant to silica sol is (0.2~3):100; The mass ratio of opaque particles to silica sol is (0.5~6):100; The average diameter of the opacifier particles ranges from 0.4 to 6 μm.

5. The preparation method according to claim 1, characterized in that, In step S2, the surfactant is any one of sodium oleate, sodium alkyl succinic anhydride, sodium cocoate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium secondary alkyl sulfonate, dodecyl trimethyl ammonium chloride, dodecyl dimethyl benzyl ammonium chloride, didodecyl dimethyl ammonium chloride, dodecyl glucoside, fatty alcohol polyoxyethylene ether glucoside, dodecyl betaine, dodecyl dimethyl ammonium chloride, dodecyl dimethyl ammonium oxide, fatty alcohol polyoxyethylene ether, and dodecylphenol polyoxyethylene ether; The opacifier particles are any one of silicon carbide, zirconium oxide, titanium oxide, boron carbide, and boron nitride.

6. The preparation method according to claim 1, characterized in that, Step S3 is as follows: Under normal pressure, ceramic fiber felt is immersed in silica sol containing a light-blocking agent for 0.5 to 30 minutes to gel, and then kept at room temperature to 75°C for 0.5 to 2 hours to obtain fiber felt / gel composite. Among them, ceramic fiber felt is any one of alumina fiber felt, mullite fiber felt, high silica fiber felt, aluminum silicate fiber felt, and quartz fiber felt.

7. The preparation method according to claim 1, characterized in that, In step S4, the drying process specifically involves placing the fiber felt / gel composite in a supercritical drying vessel and sealing it, using carbon dioxide fluid as the drying medium. The temperature inside the vessel is 40~80℃, the pressure is 10~25MPa, and the holding time is 6~24h.

Citation Information

Patent Citations

  • Preparation method of alumina aerogel heat insulation felt

    CN117779443A